Parkinson’s Disease Quality of Life: Disease Severity Outweighs Pain Impact - Raisa, Neila; Maziya, Yulianda; Rahma, Annisa; Harbiyanti, Novita Titis; Kurniawan, Shahdevi Nandar (poltekkes kemenkes mataram, 2024)
Introduction: Parkinson's disease is the second most common neurodegenerative disorder after Alzheimer's disease, progressively affecting both motor and non-motor systems in patients. In addition to the commonly recognized motor symptoms such as tremor, rigidity, and bradykinesia, non-motor symptoms such as chronic pain are often underdiagnosed. Pain in Parkinson's patients can manifest in various forms, including musculoskeletal pain, neuropathic pain, and dystonic pain. While pain is not a primary symptom defining Parkinson's, its impact on patients' quality of life is profound, contributing to reduced mobility, sleep disturbances, increased risk of falls, and poor mental health, including depression and anxiety. This study aimed to explore the relationship between the severity of Parkinson's disease, pain levels, and quality of life in Parkinson's patients. Method: A cross-sectional observational study was conducted at the Neurology Clinic of RSUD Dr. Saiful Anwar in East Java from October 2023 to March 2024, using purposive sampling techniques. We assessed Parkinson's severity (Hoehn & Yahr scale), pain levels (Numeric Rating Scale), and quality of life (Parkinson's Disease Questionnaire-39 (PDQ-39) Indonesian Version). Result: The study found that PDQ-39 INA scores were significantly associated with Parkinson's disease severity (n = 11, p = 0.012), indicating a significant impact of disease severity on quality of life. However, no significant relationship was found between PDQ-39 scores and pain levels (p = 0.117). Pearson correlation analysis showed no significant relationship between Parkinson's severity scale and pain level (r = 0.461, p = 0.154). Specifically, Parkinson's severity significantly affected PDQ-39 scores (p = 0.001), while pain levels did not have a significant effect (p = 0.399). Conclusion: This study reveals that while pain is a critical issue, it is the severity of Parkinson's disease that has a more substantial impact on patients' quality of life.